THE SOCIAL AND POLITICAL EFFECTS OF POPPY CULTIVATION IN AFGHANISTAN - Святуха, І.А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
A look at the main causes and factors, as well as the historical dynamics of drug production evolution in Afghanistan. The Talihban movement’s influence on mass poppy cultivation and production is shown. The research focuses on the economic effects of poppy production for the population, as well as the amount of local citizens taking part in the production process. It is proved that poppy cultivation has become a necessary survival strategy for afghan lower-class due to lack of similar paying labour within the country.